2012
DOI: 10.1021/es300797z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feedstock and Pyrolysis Temperature of Biochar Amendments on Transport ofEscherichia coliin Saturated and Unsaturated Soil

Abstract: The effects of biochar feedstock, pyrolysis temperature, and application rate (1 and 2%) on the transport of two Escherichia coli isolates through a fine sand soil under water-saturated and partially saturated conditions were investigated in column experiments. Biochars from two feedstocks (poultry litter and pine chips) and pyrolyzed at two temperatures (350 and 700 °C) were evaluated. Both biochars pyrolyzed at 700 °C resulted in significant reductions in E. coli transport, with greater reductions observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 44 publications
7
60
0
Order By: Relevance
“…One mode of human exposure to these pathogens is through consumption of fecal contaminated groundwater [63,64]. Transport of microbial pathogens into ground water sources may be significantly reduced by application of biochar [9,10]. Those researchers evaluated transport of three different E. coli isolates through laboratory column that were packed with a fine sandytextured soil and then amended with poultry litter biochar produced at two different pyrolysis temperatures (350 or 700°C).…”
Section: Biochar Impact On Pathogen Transport and Microbial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One mode of human exposure to these pathogens is through consumption of fecal contaminated groundwater [63,64]. Transport of microbial pathogens into ground water sources may be significantly reduced by application of biochar [9,10]. Those researchers evaluated transport of three different E. coli isolates through laboratory column that were packed with a fine sandytextured soil and then amended with poultry litter biochar produced at two different pyrolysis temperatures (350 or 700°C).…”
Section: Biochar Impact On Pathogen Transport and Microbial Propertiesmentioning
confidence: 99%
“…For example, Novak et al [8] reported that biochar produced from poultry litter had a negative impact on shallow ground water quality by releasing significant concentrations of dissolved phosphorus and by increasing movement of fecal bacteria through the soil [9,10]. On the other hand, biochar produced from pine chips significantly decreased movement of fecal bacteria through fine sand [9].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar can be used as an activated carbon when its pore structure and surface area are appropriate [14]. In addition, biochar can act as a soil conditioner enhancing plant growth, and more importantly, retain nutrients and provide other benefits such as improvement of soil physical and biological properties [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of biochar into soils offers the opportunity for simultaneous application of plant beneficial microorganisms (Hale et al 2014). Biochar properties vary depending on feedstock and production methods, but many biochars have characteristics that are also conducive for use as inoculum carriers, including high internal porosity, large specific surface area, and the ability to adsorb organic compounds and microorganisms (Abit et al 2012).…”
Section: Conclusion and Application Trendsmentioning
confidence: 99%